Patterns of nitrogen and phosphorus conservation in dominant perennial grasses and shrubs across an aridity gradient in Patagonia, Argentina - Bertiller, Monica Beatriz (2005)
The aim of this study was to assess the patterns of N and P conservation in dominant perennial grasses and shrubs across an aridity gradient in Patagonia. We analysed leaf dry mass per area, and N and P concentrations in green leaves and N and P resorption from senescing leaves in dominant species of each life-form across the gradient. Leaf dry mass per area and concentration of N and P in green leaves did not differ between life-forms, whereas, increasing N concentration in green leaves of perennial grasses and decreasing P concentration in green leaves of shrubs were related to the severity of aridity. Perennial grasses showed lower N concentration in senesced leaves, and higher N- and P-resorption efficiency than shrubs. In shrubs, N-resorption efficiency decreased with aridity while N concentration in senesced leaves increased with aridity. On the contrary, traits in senesced leaves of perennial grasses did not vary across the aridity gradient. These differences in the patterns of N and P conservation between life-forms are of adaptive significance and relevant in relation to decomposition pathways and nutrient cycling in the studied arid ecosystems.